Effectiveness of Qur’anic Tahfiz Program Enhancing Islamic Character at SMP IT Asy Syafiiyah Garut - Hari Sahrudin; Ahmad Sukandar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the effectiveness of the Qur'anic Tahfiz Program in enhancing the Islamic personality of students at SMP IT Asy Syafiiyah, Leuwigoong, Garut Regency, focusing on religiosity, moral conduct, discipline, and the internalization of Qur'anic values. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews with teachers, students, and parents, and analysis of curriculum documents and memorization achievements. The findings show significant improvements: a 43% increase in prayer discipline, religiosity scores 78% higher among Tahfiz students compared to the control group, and an 82% increase in spiritual intelligence (SQ) based on a modified SISRI-24. The Tahfiz-Based Character Education (TBCE) model integrating mnemonic moral coding, contextual tafsir application, and spiritual journaling proved effective in connecting memorization with the practice of Islamic values, as confirmed by 92% of teachers. Key success factors included hierarchical memorization, certified multidisciplinary teachers, and spaced repetition technology. However, 65% of parents lacked the capacity to support muroja’ah at home. The study concludes that Tahfiz programs foster holistic Islamic personality development and recommends parental coaching, neuroscience integration, and hybrid learning models